Stabilizing Teeth with non Surgical Treatment: A Case Report of Splinting - Susant Mohanty1 , Sonu Acharya2 , Jnana Ranjan Swain3 , Bismay Singh3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
The management of tooth mobility is one of the prime objectives of traumatic injury. The treatment oftrauma-associated tooth mobility may include occlusal therapy, extraction, splinting and various treatmentstoo. This article discusses a case report on the management of tooth mobility in trauma associated patients.